2011
DOI: 10.1007/s00198-011-1528-y
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal mineralization defects in adult hypophosphatasia—a clinical and histological analysis

Abstract: Taken together, our data show that adult hypophosphatasia does not solely result in an enrichment of osteoid, but also in a considerable degradation of bone quality, which might contribute to the increased fracture risk of the affected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 36 publications
1
41
1
3
Order By: Relevance
“…Alpl encodes tissue-nonspecific alkaline phosphatase, which is responsible for the hydrolysis PP i , (50) and Alpl expression has been shown previously to be regulated by extracellular adenosine. (27) In humans, disruption of ALPL causes hypophosphatasia, characterized by skeletal hypomineralization (56) and presumably a result of excessive accumulation of PP i . Thus, decreased Alpl expression in the spinal tissues of ENT1 -/-mice would be expected to increase extracellular PP i levels, counteracting the decrease in PP i arising from changes in Enpp1 and Ank expression.…”
Section: Discussionmentioning
confidence: 99%
“…Alpl encodes tissue-nonspecific alkaline phosphatase, which is responsible for the hydrolysis PP i , (50) and Alpl expression has been shown previously to be regulated by extracellular adenosine. (27) In humans, disruption of ALPL causes hypophosphatasia, characterized by skeletal hypomineralization (56) and presumably a result of excessive accumulation of PP i . Thus, decreased Alpl expression in the spinal tissues of ENT1 -/-mice would be expected to increase extracellular PP i levels, counteracting the decrease in PP i arising from changes in Enpp1 and Ank expression.…”
Section: Discussionmentioning
confidence: 99%
“…The adult form of hypophosphatasia is mainly characterized by osteomalacia, pseudofractures, and pathologic fractures after minimal trauma, as well as by muscle and joint pain (55). In addition, a study demonstrated that histomorphometry and quantitative backscattered electron microscopy of iliac crest biopsies from patients with adult hypophosphatasia confirmed the expected enrichment of non-mineralized osteoid, but also showed an altered trabecular microarchitecture, an increased number of osteoblasts, and an impaired calcium distribution within the mineralized bone matrix (56). Hypophosphatemic nephrolithiasis/osteoporosis-1 (NPHLOP1) is caused by heterozygous mutation in the sodium/phosphate cotransporter type 2 (SLC34A1) gene (prevalence <1/1.000.000).…”
Section: Metabolic Bone Diseasementioning
confidence: 92%
“…The pathogenesis of osteoporosis in this disease is not clear, however increased bone turnover and impaired trabecular bone microarchitecture have been described (64). The risk of fractures seems correlate with acromegaly activity, its duration, coexistent hypogonadism, diabetes mellitus, and glucocorticoid therapy (56). There are no specific recommendations, but screening with thoracic and lumbar vertebral radiographs is indicated in patients affected by acromegaly (64).…”
Section: Acromegalymentioning
confidence: 99%
“…Common disease manifestations of HPP in adults are, in particular, metatarsal and femoral stress fractures or pseudofractures, pathological fractures after minimal trauma, muscle and joint pain, and osteomalacia (18,19). However, the incidence and clinical manifestation of the latter may also be complicated by an additional vitamin D deficiency, which is frequently seen in HPP patients (20).…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence and clinical manifestation of the latter may also be complicated by an additional vitamin D deficiency, which is frequently seen in HPP patients (20). In addition to the above clinical symptoms, the diagnosis of HPP is based on low serum ALP enzyme activity, high endogenous levels of TNSALP substrates, and ultimately mutations in the ALPL gene (9,18).…”
Section: Introductionmentioning
confidence: 99%